PENGARUH MODEL KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 1 PALU - Nining Nining (Katalogis, 2016)
This research aims at analyzing the influence of cooperative model of make a match in improving the student’s learning outcomes on history subject at SMA Negeri 1 Palu. 80 students were taken as research samples; 40 grade eleventh students of IPS 2 as a control class. The samples were taken through purposive sampling on the basis of certain criteria determined by the researcher in accordance with the research purpose. This was an experimental research applyian t-test to analyze the data. The results show that the cooperative model of make a match gives influence toward the students learning oucomes. The students were taught using cooperative model of make a match got higher score than they who were taught using a convenational learning method.